2014
DOI: 10.1002/2014gl059844
|View full text |Cite
|
Sign up to set email alerts
|

Nonmigrating tidal variability in the SABER/TIMED mesospheric ozone

Abstract: This paper presents for the first time evidence showing nonmigrating tidal variations in the mesospheric ozone (O 3 ) derived from the Sounding of the Atmosphere using Broadband Emission Radiometry/Thermosphere-Ionosphere-Mesosphere-Energetics and Dynamics (SABER/TIMED) for a full 11 year period, 2002-2012. The O 3 tidal fields are extracted from the data by the same method as the temperature tides have been derived. The spatial distribution and seasonal variability of the three strongest nonmigrating O 3 tida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This is consistent with previous findings, for example, Liu et al () reports the modulation of tides in temperature and winds by the QBO using Ground‐to‐topside Atmosphere‐Ionosphere model for Aeronomy. Pancheva et al () have also reported similar findings in the DE3 tidal fields in mesospheric ozone. El Niño‐Southern Oscillation (ENSO) signals can also be observed in the DE3 amplitudes (Figure ).…”
Section: Tidal Diagnostics Of Saber No 53 μM and Co2 15 μM Cooling Rsupporting
confidence: 61%
“…This is consistent with previous findings, for example, Liu et al () reports the modulation of tides in temperature and winds by the QBO using Ground‐to‐topside Atmosphere‐Ionosphere model for Aeronomy. Pancheva et al () have also reported similar findings in the DE3 tidal fields in mesospheric ozone. El Niño‐Southern Oscillation (ENSO) signals can also be observed in the DE3 amplitudes (Figure ).…”
Section: Tidal Diagnostics Of Saber No 53 μM and Co2 15 μM Cooling Rsupporting
confidence: 61%
“…Due to the slow precession of the TIMED satellite, it takes nearly 60 days to get full local time coverage. With the SABER data of the 60 days resolution, there have been several studies on the tides in temperature and ozone in the low and midlatitudes middle atmosphere (Li et al, ; Mukhtarov et al, ; Pancheva et al, ; Xu et al, ; Zhang et al, to state a few). However, the mesospheric tidal variabilities over low latitudes and their relation with the source variabilities are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This secondary ozone maximum (as compared to the original stratospheric ozone maximum) results from the combined effects of the atomic oxygen maximum at the mesopause and the prevailing very low temperature that affect chemical rate coefficients and atmospheric density (Smith & Marsh, ). Above 80 km, there is a very clear semiannual oscillation signal marked by the highest ozone values seen around the equinox times, when the diurnal tide amplitude is largest (Pancheva et al, ; Smith et al, ). Using a migrating diurnal tide model, Smith et al () demonstrated that the associated upward motions cool the air adiabatically and bring low concentrations of atomic oxygen and hydrogen from below.…”
Section: Methodsmentioning
confidence: 99%